El discurso de Benedicto XVI en la Universidad de Ratisbona y las reacciones provocadas - Corral, Carlos (UNISCI Discussion Papers, 2006)
One of the paragraphs in Benedict XVI’s address to the scholars at Ratisbona (Regensburg) University, divulged by the Qatari news channel Al Jazeera, provoked angry reactions and diplomatic conflicts. That is why we ask, which address and paragraph motivated this argument? And what were the reactions and counter-reactions?